Pengaruh Model Pembelajaran Problem-Based Learning (PBL) Berbasis Artificial Intellingence (AI) Terhadap Kemampuan Berpikir Kritis Siswa - Al Ahzuri; Astuti Astuti; Zulfah Zulfah (Pendidikan Matematika FKIP Universitas Mataram, 2026)
21st-century education demands that students possess critical thinking skills to navigate informational complexities and global dynamics. However, many educational systems remain predominantly focused on content mastery. While content knowledge is essential, the 2018 PISA results indicated that Indonesian students scored below the average in critical thinking proficiency. One effective approach to stimulate these skills is the Problem-Based Learning (PBL) model, which, when supported by technology such as Artificial Intelligence (AI), can enhance personalized learning. This study aims to investigate the effect of integrating AI into the PBL model on students' critical thinking skills at SMA Muhammadiyah Bangkinang. Utilizing a Nonequivalent Control Group experimental design with pre-test and post-test evaluations, the study involved two classes, where the experimental class received AI-based PBL treatment. The results demonstrated a significant increase in the critical thinking skills of the experimental class compared to the control class, yielding an effect size of 1.165, which indicates a high treatment effect. Observations of student activities also revealed enhanced engagement and collaboration. The conclusion of this study confirms that the AI-based PBL model is an innovative and effective method for improving students' critical thinking skills, encouraging them to be more active and creative in problem-solving.The implementation of this method is expected to provide practical contributions to instructional strategies relevant to the 21st century.